Examining the Impact of Digital Leadership on Innovative Work Behavior and Knowledge Sharing Behavior Through Psychological Ownership - Sebetci, Özel; Çavuş, Muhammet Nimet; Çavuş, Baran (International journal of sociotechnology and knowledge development, 2025)
This study investigates the impact of digital leadership on employees' innovative work behavior and knowledge sharing behavior, with a particular focus on the mediating role of psychological ownership. The independent variable, digital leadership, is examined through its supportive and innovative sub-dimensions, while psychological ownership is explored through emotional and work-based ownership. The dependent variables are innovative work behavior and knowledge sharing behavior. To test the research model, eight sub-models were developed and analyzed using PLS-SEM. Mediation was assessed through the Variance Accounted For (VAF) metric. Data were collected from 287 managers and employees working in IT departments within technology parks located in Ankara, Türkiye. The results reveal that both supportive and innovative forms of digital leadership have a positive and statistically significant influence on employees' innovative behavior and knowledge sharing. However, a portion of this effect operates indirectly through psychological ownership.